CORRELATION BETWEEN NUCLEUS FACTOR KAPPA B AND MICROVESSEL DENSITY IN NASOPHARYNGEAL CARCINOMA - Farrel; Izry Naomi Tobing; Fahat; Rizalina A Asnir; Adlin Adnan (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2020)
Abstract Introduction: Nasopharyngeal carcinoma (NPC) is an aggressive head and neck cancer, mostly associated with EBV infection. Nuclear factor kappa B (NF-κB) is transcription factors that act as a tumor promoter, especially in inflammation-associated cancer. It also attracts angiogenesis. Microvessel Density (MVD) is widely used as an index for tumor angiogenesis. There have been no studies found about the correlation of NF-κB and MVD expression in NPC. Objective: The aim of this study is to investigate the correlation of NF-κB and MVD expression that may affect targeted therapies in NPC patients Methods: A total of 30 paraffin blocks of NPC patients biopsies were assessed immunohistochemically for NF-κB expression and MVD. Data were analyzed using the Spearman's nonparametric test to assess the correlation between NF-κB expression and MVD. Results: Positive NF-κB expression was found in 22 (73.33%) patients and negative in 8 (26.67%) patients. High MVD expression in 17 (56.67%) patients and low MVD expression in 13 (43.33%) patients. There was no significant correlation found between NF-κB and MVD. Conclusion: This study has not confirmed any correlation between NF-κB and MVD. Further research needs to be done to get a better assessment on nuclear proliferation rates and tumor-related angiogenesis in NPC.